The effect of urea manuring addition with different doses on the abundance of density Nannochloropsis sp. - Hasibuan, Saberina; Pamukas, Niken Ayu; ', Riduan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research has been conducted from the February 28th until March 14th, 2015 at laboratory of the Marine Aquatic Culture Center of Batam, Setoko Island, District Bulang, Barelang. The purpose of this study was to determine the effects of different doses of urea for the growth of Nannochloropsis sp. The method used in this research was experimental method by using a completely randomized design with four treatments and three replications. The treatment in this study were P0 ( control ), P1 ( Urea fertilizer dose of 40 ppm, 20 ppm TSP, Za 50 ppm, 10 ppm EDTA ), P2 ( urea fertilizer dose of 60 ppm, 20 ppm TSP, Za 50 ppm, 10 ppm EDTA ), and P3 ( 70 ppm dose of fertilizer urea, TSP 20 ppm, 50 ppm Za, 10 ppm EDTA ). The results showed that the best growth of Nannochloropsis sp. was that on P3 treatment with growth density of 42.872 cells / litersKeyword :Nannochloropsis sp,growth of density, urea fertilizer